Application of Rare Earth Cation-Exchanged Nanozeolite as a Support for the Immobilization of Fungal Lipase and their Use in Biodiesel Production - de Paula Guarnieri, Guilherme [UNESP]; de Vasconcellos, Adriano [UNESP]; de Moraes, Fábio Rogério [UNESP]; Nery, José Geraldo [UNESP] (Wiley, 2021)
For the last 50 years, zeolite ions exchanged with lanthanum (La3+) and cerium (Ce3+) rare earth cations have mostly been used as fluid catalytic cracking catalysts (FCCs) in the petrochemical industries for the production of fuels. However, environmental concerns and restrictive legislation have led researchers to develop clean technologies for energy production of biofuels such as biodiesel from renewable sources. In this context, a new class of biocatalysts composed of nanozeolite ions exchanged with rare earth cations (La3+, Ce3+, Gd3+, Dy3+) and fungal lipases such as Thermomyces lanuginosus lipase (TLL) and Rhizomucor miehei lipase (RML) has been applied as heterogeneous catalysts for the transesterification of non-edible microalgae oils to fatty acid ethyl esters (FAEEs). Experimental results indicate that TLL immobilized on rare earth nanozeolitic supports showed more activity in comparison with RML. Considering these facts, this chapter looks at such parameters as amount of immobilized enzyme, enzymatic activity, and FAEE yield, along with bioinformatics approaches and the different behaviors of both nanozeolite–enzymes complexes (TLL and RML).
Keywords: biodiesel and microalgae; bioinformatics; enzyme immobilization; nanozeolites; rare earth chemistry